Copyright Law Protection in Metaverse, The Sandbox Based on Positive Law in Indonesia - Ghina Nabilah; Miranda Risang Ayu Palar; Helitha Novianty Muchtar (Jurnal Indonesia Sosial Teknologi, 2024)
Metaverse, as one of the innovations of technological developments, can present copyright in it, such as the existence of NFTs in The Sandbox metaverse. The existence of NFTs as digital copyrights in The Sandbox raises problems, one of which is that legal regulations in Indonesia need to regulate the ownership and position of NFTs clearly, and no system can confirm the authenticity of these NFTs. This study aims to determine the protection of NFTs in The Sandbox metaverse and to find out the technical settings in The Sandbox metaverse to protect NFTs based on legal, technological, and theoretical aspects used in research. This research uses normative juridical methods by analyzing laws, regulations, and legal literature. Although not explicitly regulated in Indonesia's positive law, NFT as a digital work in The Sandbox is an object of copyright referring to the Copyright Law. Electronic systems may seek the use of architecture or technology ("code") in conjunction with market modalities, social norms, and laws to protect copyright